PROFESSIONAL TEACHER PROGRAM EXPERIENCE: TEACHERS’ KNOWLEDGE ON OVERCOMING STUDENTS’ MISCONCEPTION - Fahruh Juhaevah; Patma Sopamena; Syafruddin Kaliky (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
This study aims to describe the teachers’ knowledge about students in dealing with misconceptions experienced by the student on integral material based on the experience of teachers participating in the teacher professional program (PPG). This research is qualitative research that involved two subjects who were mathematics teachers of SMA Negeri 11 Ambon. Subjects were given a chance to identify the student's misconceptions. The data is collected through observation and interviews. Based on the research results obtained information that S1 has good knowledge in diagnosing misconceptions when use three tiers test, providing treatment when the student got a different answer, and ensuring that misconceptions do not occur in student with made peer instruction in front of the class, and have a good understanding of concepts about means of constant on indefinite integral. S2 cannot diagnose misconception and S2 cannot explain the different answers when the student solves the problem using a different method. Thus, it can be stated that teachers who have the PPG experience have a better knowledge of knowing and addressing the misconceptions experienced by the student.